Phenolic Plant Extracts Versus Penicillin G: In Vitro Susceptibility of Staphylococcus aureus Isolated from Bovine Mastitis - Fernanda Gomes; Maria Elisa Rodrigues; Natália Martins; Isabel C.F.R. Ferreira; Mariana Henriques (MDPI AG, 2019)
Antibiotics are the elective drugs in bovine mastitis (BM) treatment, despite their low rates of efficiency and effectiveness and increasing risk of pathogen resistance. In this sense, it is urgent to discover new and effective antimicrobial agents to apply in BM control and even treatment. Plant extracts have been widely recognized as a rich source of phytochemicals with antimicrobial potential. Thus, the present work aims to compare the bioactivity of Eucalyptus globulus and Juglans regia extracts against Staphylococcus aureus bovine mastitis strains with penicillin G. At non-toxic concentrations, E. globulus exerted a bacteriostatic effect in planktonic cells and J. regia had no antimicrobial activity. Penicillin G, at minimum inhibitory concentration (MIC), demonstrated bactericidal activity, but just for S. aureus 3, 5, 6 and ATCC 25923, while the other strains seem to have acquired resistance. On the other hand, E. globulus and penicillin G in combination demonstrated synergy, being the most effective approach against S. aureus 1, 2 and 4. Thus, penicillin alone and in combination with E. globulus or J. regia seems to be promissory strategies to control bovine mastitis infections.